Solvent Extraction and Electrowinning of Copper from Hot Rolling Mill Scale Liquor - Gohar, Rehmat Ali; Ahmad, Sameer; Khan, Asma Haleem (Biological Sciences - PJSIR, 2006)
The Acorga M5640 solvent extraction reagent was used for the extraction of copper from hot rolling mill scale liquor. The copper concentration in this liquor ranged between 2 g per litre to 14 g per litre. Ten g per litre Cu and 3 g per litre Fe of the prepared initial feed was used in the solvent extraction and electrowinning unit. Six g per litre Cu in the aqueous solution was used during laboratory scale experimentation because the lower strength was almost completely loaded in the organic extractant, Acorga M5640. The conditions optimized were: organic phase of 30% (v/v) in kerosene and the loaded organic extractant was 5.43 g per litre at 90.5% extraction; pH 2.5; extraction aqueous to organic phase ratio of 5:1 and stripping aqueous to organic phase ratio of 3:1; extraction cycle performance 3 and stripping cycle performance 2; and phase disengagement and equilibration time 10 min. The electrolyte containing sulphuric acid, 35 g per litre in combination with varying amounts of copper sulphate ranging from 25 g per litre to 40 g per litre was used as the strip solution on laboratory scale. Atomic absorption spectrophotometry and electrogravimetric analysis were used for the determination of electrowon copper, which in the present study were 99.89% and 99.78%, respectively. The solvent stability and reliability was excellent, which was also verified by the results achieved during the bench scale study for further use in solvent extraction mixer-settler counter-current unit.